Livelihood Expansion and Local People’s Expectations in the Realm of China-Pakistan Economic Corridor in Hunza, Gilgit Baltistan, Pakistan - Bano, Tehzeeb; Khayyam, Umer; Alam, Arif (European Journal of Sustainable Development, 2019)
Economic Corridors around the world has been creating livelihood opportunities for people thus stimulating economic growth and development. This study has explored the opportunities for livelihood expansion which exists in the China Pakistan Economic Corridor (CPEC) for the people of Gilgit Baltistan (GB), as the region lacks many vital livelihood opportunities. CPEC is considered as a fate changer, specifically for the people of Hunza valley, which provides the pathway to CPEC emanating from China to the rest of Pakistan. The economic growth process in the region is now been linked with the expansion of livelihood opportunities to benefit the local poor. This study has deployed quantitative research technique and used purposive sampling technique for field survey. Results show that a major bulk – 60% of the local respondents, 70% members of GBLA and 80% of the members of Chamber of Commerce in Hunza (Gilgit Baltistan) are hopeful that CPEC will create employment opportunities for local community. Due to high potential of GB in tourism sector, a high number of respondents (53%) expected that tourism sector will develop through CPEC while 28% of the local people and the members of Chamber of Commerce expected that industrial sector will get boost through CPEC, 19% of the respondents were having opinion that agriculture sector will develop through this mega project creating employment opportunities for the local youth in their native area. Keywords: CPEC, Gilgit Baltistan, employment opportunities, tourism, small industries.